Road Geometric Redesign of Horizontal Alignment on Kunciran–Serpong Toll Road Using AutoCAD® Civil 3D - Shofie Rania Salsabila; Amanatullah Savitri (LEADER: Civil Engineering and Architecture Journal, 2023)
Transportation network systems are designed to provide efficient connectivity between various locations. The toll road is a transportation network system connecting one area to another. As a freeway, toll roads must have a higher safety level than regular roads. Therefore, geometric road planning must be done carefully so that the toll road can provide safety and comfort. Currently, applications are used to get accurate calculations and speed up processing time. In this paper, geometric redesign especially on horizontal alignment on Kunciran‒Serpong toll road using AutoCAD® Civil 3D. The Kunciran - Serpong toll road is part of the Jakarta Outer Ring Road (JORR) network that connects Banten to Jakarta. The secondary data for coordinates and contour data were obtained from Google Earth® and processed using the Global Mapper®. The design result shows that the Kunciran‒Serpong toll road is a primer arterial road class I, with a 4/2-T road type. The horizontal alignment is designed as a Full Circle (F-C) type arch on both bends (PI1 and PI2), with a total length value is 3819.286 m, a planned radius value is 600 m and a velocity design of 100 km/h. Using AutoCAD® Civil 3D to design and calculate the road geometric helps to receive accurate results and is more efficient than the manual method.